Direitos Humanos e a Política Internacional: O Caso Da Guerra Civil Do Iêmen - SILVA, Lorena Ribeiro Da (Universidade Federal do Tocantins, 2023)
In contemporary times, where the increase of internal armed conflicts has been increasingly observed, an ongoing combat that has its roots in the Arab spring will be studied in this work. The people of Yemen, a country located in the Middle East, suffer from the war of the current government, backed by a military coalition led by Saudi Arabia, against a rebel militia from the Houthi family. As this conflict is still ongoing, the temporal delineation of this serious study from the beginning of the war in 2015 to 2019. The Hadi government and its supporters denounce Iran's involvement in the war by giving aid to the rebels. denied by the parties. The historical context preceding the war is evidenced to demonstrate the main relevant events and to understand the reasons why the country is at war. The purpose of this paper is to expose the human rights violations of the civilian population in war, especially by the government that has a duty to protect citizens within Yemeni territory. In addition, violations of international humanitarian law will be pointed out, as well as the disadvantages of an international system based on the guidelines of neoliberalism at the height of globalization.